Perspective on Cerebral Autoregulation Monitoring in Neonatal Cardiac Surgery Requiring Cardiopulmonary Bypass - Spilka, Jared M.; O'Halloran, Conor P.; Marino, Bradley S.; Brady, Kenneth M. (Frontiers in Neurology, 2021)
The autoregulation of cerebral blood flow protects against brain injury from transient fluctuations in arterial blood pressure. Impaired autoregulation may contribute to hypoperfusion injury in neonates and infants. Monitoring cerebral autoregulation in neonatal cardiac surgery as a guide for arterial blood pressure management may reduce neurodevelopmental morbidity. Cerebral autoregulation monitoring has been validated in animal models and in an adult trial autoregulation monitoring during bypass improved postoperative delirium scores. The nuances of pediatric cardiac disease and congenital heart surgery make simply applying adult trial findings to this unique population inappropriate. Therefore, dedicated pediatric clinical trials of cerebral autoregulation monitoring are indicated.